Dissenting Opinion Pengangkatan Anak oleh Kakek Kandung Analisis Putusan Pengadilan Agama Demak No.0033/Pdt.P/2010/PA.Dmk - Nabila, Khofifah; Harahap, Mhd Yadi (Universitas Ekasakti, 2023)
Adoption or what is known as adoption or tabanni is the adoption of someone else's child as their own child but the biological parents do not necessarily let go of their hands, only that they will still have a relationship with their child. According to Government Regulation no. 54 of 2007 concerning Implementation of Child Adoption. This research applies a normative juridical method (Legal Research), which is a type of research used to examine the rules or norms in positive law. After conducting this research, the results obtained were that there was a Dissenting Opinion regarding the decision in the case of appointing a grandson as an adopted child, where the opinion of the Member Judge was afraid that there would be problems regarding inheritance if it was granted and the opinion of the Chief Judge of the Panel could be granted for the benefit of the child himself, without sever the lineage relationship with the biological parents as well as the prospective adoptive parents of the same religion as the child concerned or the same religion as the biological parents of the child concerned if the child is still small.